2017
DOI: 10.1002/berj.3276
|View full text |Cite
|
Sign up to set email alerts
|

The early academic progress of children with special educational needs

Abstract: Children with special educational needs (SEN) are known to experience lower average educational attainment than other children during their school years. But we have less insight into how far their poorer educational outcomes stem from their original starting points or from failure to progress during school. The extent to which early identification with SEN delivers support that enables children who are struggling academically to make appropriate progress is subject to debate. This is complicated by the fact t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 25 publications
(42 reference statements)
1
13
0
4
Order By: Relevance
“…The paper complicates dominant emerging academic accounts that emphasise the interconnections between poverty, hardship, and SEND. We found that young people in our case‐study areas with SEND diagnoses are more likely to come from “poor” backgrounds, being eligible for FSM, in line with broader arguments in social science (Parsons & Platt, ). Conversely, our findings show a complicated intersection between economic and cultural capital, SEND diagnoses and education, in which the spatial contexts of specific LAs and schools play an important part.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The paper complicates dominant emerging academic accounts that emphasise the interconnections between poverty, hardship, and SEND. We found that young people in our case‐study areas with SEND diagnoses are more likely to come from “poor” backgrounds, being eligible for FSM, in line with broader arguments in social science (Parsons & Platt, ). Conversely, our findings show a complicated intersection between economic and cultural capital, SEND diagnoses and education, in which the spatial contexts of specific LAs and schools play an important part.…”
Section: Discussionsupporting
confidence: 83%
“…There is a quantitative link between SEND, socio-economic disadvantage, and the reproduction of educational inequalities (Parsons & Platt, 2017). Keslair and McNally (2009) use the 2006 Schools Annual Census to emphasise that relatively high proportions of young people in all SEND categories in England are entitled to free school meals (FSM), an accepted, though imperfect, measure of poverty (Ilie, Sutherland, & Vignoles, 2017).…”
Section: Education Inequalities and (Re) Producing Privilege: Thementioning
confidence: 99%
“…Empirical evidence suggests that disabled children and young people in England perform consistently worse academically than their non‐disabled peers, with disability gaps already formed during primary school (Parsons and Platt ; Department for Children, School, and Families ; Keslair, Maurin, and McNally ). Low attainment is common among students with different types of disabilities, including those whose special educational needs require specialist support beyond that available in mainstream teaching provision in English schools (Blatchford et al ; Crawford and Vignoles ).…”
Section: Introductionmentioning
confidence: 99%
“…Low attainment is common among students with different types of disabilities, including those whose special educational needs require specialist support beyond that available in mainstream teaching provision in English schools (Blatchford et al ; Crawford and Vignoles ). However, lower attainment is only partly related to lower cognitive ability (Parsons and Platt ). A recent report showed that children with special educational needs in England are between 7 and 15 times less likely than their peers to reach key national examinations ‘benchmarks’ from early years through to age 16 (Department for Children, School, and Families ).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, we construct a ‘value‐added’ score that captures the progress made by a child at the second time point relative to those who had a similar initial score (e.g. Parsons & Platt, , ).…”
Section: Methodsmentioning
confidence: 99%